Austria : Financial Sector Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2013)
This Financial Sector Stability Assessment report reviews economic development and different fiscal policies in Austria. The global crisis has revealed weaknesses in Austria's financial stability policy framework, and recent changes at the European levels provide an opportunity to address these. Stress test results indicate that under adverse medium-term scenarios, virtually all Austrian banks, including all internationally active institutions, would meet regulatory capital requirements, and are resilient to funding and contagion risks. The Austrian Financial Market Authority (FMA) and the central bank (OeNB) collaborate effectively in performing banking supervision, including on a cross-border basis.